Chasing the dragon : assessing China's system of export controls for WMD-related goods and technologies - Medeiros, Evan S. (Rand Corporation ;, 2005)
China's export controls on sensitive equipment, materials, and technologies used to produce weapons of mass destruction (WMD) have evolved significantly since the early 1980s. This monograph examines the structure and operation of the Chinese government's system of controls on exports of items that could be used in the production of WMD and WMD-related delivery systems. The author identifies the key organizations involved in export control decisionmaking, the laws and regulations that form the basis of the Chinese government's system of controls, and the interactions among government organizations involved in vetting sensitive exports. The author assesses the strengths and weaknesses of the system's ability to implement and enforce government export controls and identifies several challenges that the Chinese government currently faces in improving the current functioning of its nascent export control system.